Impact of environmental proactivity on firm performance in Malaysia - Bah, Saiku Mayat (2011)
In spite of the significant amount of work that has been conducted to investigate the effect of environmental proactivity on firm financial performance, limited research has focused on other firm performance outcomes such as operational performance and stakeholder satisfaction. The roles played by interacting and mediating constructs have also been largely ignored in the environmental proactivity/firm performance literature. This study thus, investigated the impact of environmental proactivity on multiple firm performance outcomes and at the same time evaluated the roles played by intervening as well as interacting factors on this relationship. Drawing on stakeholder theory and the resource-based view of the firm, this study hypothesized that environmental proactivity is positively related to (1) operational performance, (2) organizational learning, (3) environmental performance, (4) stakeholder satisfaction and (5) financial performance. The study also hypothesized that the type of technologies deployed to address environmental issues moderates the relationship between environmental proactivity and operational performance. Environmental performance was hypothesized to mediate the association between environmental proactivity and stakeholder satisfaction and stakeholder satisfaction was hypothesized to mediate the relationship between environmental proactivity and financial performance. The study was conducted in Malaysia and data was collected through self-administered questionnaires that were sent to respondents in the target sample that was drawn from a list of firms obtained from the Capital IQ database. A total of 291 usable responses were received and used for the data analysis. Structural equation modelling (SEM) was used for hypothesis testing and the results provided support for six of the eight hypotheses posited in the research framework. The findings indicated that environmental proactivity was positively related to operational performance, organizational learning, environmental performance, stakeholder satisfaction and financial performance. Significantly, the mediating role of stakeholder satisfaction was also supported by the data. However, the mediating role of environmental performance and the moderating role of types of technologies were not supported by findings. The overall findings thus seem to support the theoretical model of the research.